2011
DOI: 10.4103/0970-2113.76296
|View full text |Cite
|
Sign up to set email alerts
|

Role of sputum examination for acid fast bacilli in tuberculous pleural effusion

Abstract: Background:Sputum for acid fast bacilli (AFB) is seldom looked for in the etiological diagnosis of tuberculous pleural effusion usually due to the absence of any parenchymal lesion radiologically, but presence of tubercle bacilli in sputum may have important epidemiological and therapeutic implication.Aims:This study aims to evaluate the role of sputum examination for AFB in the patients of tuberculous pleural effusion with no apparent lung parenchymal lesion radiologically.Settings and Design:Forty-five conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Most of the patients were in the age group of 46-55 yrs and the mean age of the patients was 40.44 yrs ±11.35 yrs. This finding is comparable with the study done by A D Choudhuri, S Bhuniya, S Pandit et al 3 . and Marcus B. Conde , Angela Chindamo Loivos, Valeria et al 6 where they found male female ratio was 3:1.…”
Section: Discussion:-supporting
confidence: 82%
See 1 more Smart Citation
“…Most of the patients were in the age group of 46-55 yrs and the mean age of the patients was 40.44 yrs ±11.35 yrs. This finding is comparable with the study done by A D Choudhuri, S Bhuniya, S Pandit et al 3 . and Marcus B. Conde , Angela Chindamo Loivos, Valeria et al 6 where they found male female ratio was 3:1.…”
Section: Discussion:-supporting
confidence: 82%
“…But this was not statistically significant as the p value was >0.05. In the study all patient's pleural fluid was lymphocytic predominant while it was 95.45% in the study conducted by A D Choudhuri, S Bhuniya, S Pandit et al 3 . In the study it was found that 50% of patients with parenchymal lesions on chest radiography were positive for sputum smear for AFB while only 7.14% for whom parenchymal lesion was absent.…”
Section: Discussion:-mentioning
confidence: 99%
“…Conde et al [8] demonstrated that the yield of sputum culture was 6% to 13% higher than that described previously (4-9%) in patients with no parenchymal lesions and similar to those with lesions on chest radiograph [3,9,10]. Other similar studies from Los Angeles [11] and India [5,12] also reported a high yield of sputum induction in pleural tuberculosis.…”
Section: Discussionmentioning
confidence: 65%
“…For a confirmatory diagnosis of tuberculosis, isolation of the bacterium from pleural fluid or pleural tissue is required which is mostly not possible due to the pathogenesis of the disease [3]. It is known that pleural space infections are acquired from initial parenchymal lesions which are usually not obvious on chest radiography [4,5]. With the use of computed tomography, parenchymal lesions and focal areas of subpleural cavitation can be visualized [6].…”
Section: Introductionmentioning
confidence: 99%
“…9 On the other hand, sputum may be bacteriologically smear and/or culture positive in less than 1/3 of cases with tubercular pleural effusion. 10 Cardiac myxoma associated with Carney complex is often multicentric, occurs at a younger age and at unusual sites, and shows a higher tendency of recurrence after resection in comparison to solitary ones. Our patient had three myxomas in three different chambers of the heart, while her 6-year-old son had one solitary myxoma in the right atrium.…”
Section: Discussionmentioning
confidence: 99%